ANALYSIS OF ACQUIRED ANTIMICROBIAL RESISTANCE GENES IN GENOMES OF IRAQI ACINETOBACTER BAUMANNII - Abduljabbar, Maryam Hazem; Salih, Talal Sabhan (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aimed to investigate and analyze antimicrobial-resistant (AMR) genes in Acinetobacter baumannii isolates from Iraq, identify the frequency and proportions of resistant genes, and determine strains resistant to multiple antibiotics, including their genetic profiles based on protein-coded gene sequences. Methods: A total of 41 A. baumannii draft genome sequences were retrieved from the PATRIC database, spanning 2004–2018, and analyzed using ResFinder 4.0 for antibiotic resistance genes. Molecular typing was conducted via the Pasture MLST scheme targeting seven housekeeping genes (e.g., cpn60, fusA). Data were processed through the Center for Genomic Epidemiology for detailed resistance profiling. Results: Fifty-two known resistance genes were identified in 41 genomes. Most strains demonstrated multidrug resistance (MDR), while one strain exhibited extensive drug resistance (XDR). These findings underscore the concerning emergence of highly resistant A. baumannii strains in Iraq. Novelty: The study validates ResFinder 4.0 as an effective in silico tool for genetic analysis of AMR genes in A. baumannii, providing a comprehensive genomic epidemiological profile of Iraqi isolates. This is among the first studies to offer such detailed insights into the genetic resistance mechanisms of A. baumannii in Iraq.